MODIFIKASI VOLUME SILINDER MOTOR TOSSA 100CC MENJADI 110CC UNTUK MENINGKATKAN PERFORMA MESIN - Prasetiyo, Gatot Budy (Fakultas Teknik Universitas Wisnuwardhana, 2014)
Modification of the automotive field in recent years experienced rapid growth and diverse, especially in the modification of existing components on the machine that is on the piston. Modifications carried out aiming to obtain performance that is better than a working system in automotive vehicles.The problem that arises is how to find performance motorcycles (motor power) of the change in / modifications to the cylinder, and how to modify the cylinder in question.Methods that will be done to find the performance of the engine power (engine power) by calculating the capacity of the engine, compression ratio, the total volume of the cylinder, torque, force acting on the piston, the pressure of the combustion chamber after the new bias known to power the motor.The results are found from the calculation of the cylinder standard Vs = 97.14 cm 3, Vc = 12.14 cm3, Vt = 109.28 cm 3, F = 298.8 Newton, p = 12346.49 N/m2 and the cylinder that has been modified Vs = 109.15 cm3 , Rc = 1:9,9, Vt = 121.29 cm 3, p = 137,261.31 N/m2, F = 302.6 Newton. Can learn new standard engine power of 5.92 Kw (8.05 HP) and a modified engine power of 6 Kw (8.15 HP)